Teores e quantidade de alguns elementos no córrego Lavapés, sub-bacia do rio Sorocaba, São Paulo, Brasil - Urban, Rodrigo Custódio [UNESP]; Silva, Alexandre Marco da [UNESP]; Manfré, Luiz Augusto [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2010)
This paper aimed to analyze the seasonal ionic condition and the input and output of nutrients of a watershed with urban land use in the municipality of Sorocaba to estimate the impacts in the Sorocaba river. Water samplings were taken at two sites in a period of twelve months between 2009 and 2010. The concentration of magnesium, calcium, alkalinity, sulfate, chloride, potassium, nitrate and total phosphorus had been determined in laboratory using the titrimetric and spectrophotometric methods, for each of one of the twenty four samples collected. The results were presented in the Maucha’s ionic diagram; nutrient input and output were calculated based on the results of nitrate and total phosphorus concentrations. Observed proportional variation was not significant during the study according to Maucha’s ionic diagrams. Cation dominance order was Ca2+ > Mg2+ > K+, and anion dominance order was Alcalinity > SO42- > Cl-. The input and output of nitrate and total phosphorus was larger in the rainy months, as expected. The watershed total estimated ion values shows low influence over the Sorocaba River watershed, with values close to 5,83 ton of nitrate and 0,14 ton of total phosphorus. According to modified Carlson trophic state classification, the study area has a medium eutrophication potencial, and the Lavapés stream can be considered as mesotrophic.

Este trabalho teve por objetivo verificar a condição iônica sazonal de um córrego de ocupação predominantemente urbana localizado na cidade de Sorocaba/SP, assim como verificar as taxas de exportação de nutrientes dessa microbacia e impactos no rio Sorocaba localizado na mesma cidade. Para o estudo foram realizadas coletas de água durante 12 meses, em dois pontos de coleta, entre os anos de 2009 e 2010. As análises dos atributos químicos foram realizadas em laboratório mediante metodologias de titulometria e espectrofotometria. Os atributos verificados foram magnésio, cálcio, alcalinidade, sulfato, cloreto, potássio, nitrato e fósforo total. Os resultados foram apresentados em forma de Diagramas de Maucha para os 12 meses, enquanto os atributos nitrato e fósforo total foram utilizados para cálculo de taxas de exportação de nutrientes. Não foram observadas grandes discrepâncias sazonais pelos diagramas apresentados, em relação à proporcionalidade. A dominância geral de cátions foi a seguinte para os dois pontos: Ca2+ > Mg2+ > K+ . Enquanto a ordem de dominância dos ânions foi: Alcalinidade > SO4 2- > Cl- . As taxas de exportação da região foram maiores nos períodos chuvosos. A microbacia tem baixa influência no montante estimado para a bacia do rio Sorocaba, cerca de 5,83 toneladas de Nitrato e 0,14 toneladas de Fósforo total de um total estimado de 1706 t e 426 t respectivamente. Segundo a classificação do índice de estado trófico o córrego Lavapés é considerado como mesotrófico.
Ionic condition and input and output rates of some chemical solutes in Lavapés stream, Sorocaba, SP, Brasil
Keywords: Maucha's ionic diagram; Import of nutrients; Export of nutrients; Water quality; Taxas de exportação; Qualidade de água; Índice de estado trófico